2012
DOI: 10.1262/jrd.11-115a
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Reactivation of Expression of the Silent Maternal <i>Mest</i> Allele and Acquisition of Normal Reproductive Behaviour in a Colony of <i>Peg1/Mest</i> Mutant Mice

Abstract: Abstract. Genomic imprinting confers allele-specific expression in less than 1% of genes, in a parent-of-origin specific fashion. In humans and mice the Peg1/Mest gene (Mest) is maternally repressed, and paternally expressed. Mest is expressed in embryogenic mesoderm-derived tissues and in adult brain, and paternal mutations in Mest lead to growth retardation and defective maternal behaviour. Despite our current understanding of mechanisms associated with the establishment of imprinting of Mest and other impri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The reasons for differences between our targeted Mest mouse model and Mest tm1Lef are not well understood but could be due to differences in the genetic background of the mice, the gene targeting construct, or mutation(s) in the host ES cell used for targeting [61]. Recently it was reported that backcrossing targeted Mest tm1Lef mice 5 generations onto a129/SVJ background also eliminated the early postnatal lethality and maternal behavioral phenotypes of mice with a paternal inactivation of Mest ; however, the explanation why this occurred was not clearly defined [62]. …”
Section: Discussionmentioning
confidence: 99%
“…The reasons for differences between our targeted Mest mouse model and Mest tm1Lef are not well understood but could be due to differences in the genetic background of the mice, the gene targeting construct, or mutation(s) in the host ES cell used for targeting [61]. Recently it was reported that backcrossing targeted Mest tm1Lef mice 5 generations onto a129/SVJ background also eliminated the early postnatal lethality and maternal behavioral phenotypes of mice with a paternal inactivation of Mest ; however, the explanation why this occurred was not clearly defined [62]. …”
Section: Discussionmentioning
confidence: 99%
“…The maternal allele is silenced via extensive methylation of the promoter region, which is established after fertilization (Lefebvre et al, 1997, 1998). Methylation of the maternal allele is normally permanent, although it has been shown that heterozygous mice that do not have a functional paternal allele can show expression of Mest after E13.5, indicating that imprinting of the maternal allele can be reversed under certain conditions (Imamura et al, 2005; Ineson et al, 2012). Mest knock-out (KO) mice are viable and, apart from growth retardation, have not been reporter to show obvious phenotypic features (Lefebvre et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…MEST is a maternal imprinted gene and widely expressed throughout the embryonic period [24]. Mest-knockout mice exhibited embryonic and placental growth retardation and postnatal growth inhibition, while loss of the imprinted gene resulted in postnatal weight gain and multiple organ hypertrophy [25,26]. King et al have found that Mest speci cally expressed myocardial trabeculae in developing atria and ventricles of mice.…”
Section: Discussionmentioning
confidence: 99%